2019
DOI: 10.1111/ajag.12745
|View full text |Cite
|
Sign up to set email alerts
|

Rapid response teams to support dementia care in Australian aged care homes: Review of the evidence

Abstract: Objectives: To identify attributes of rapid response services designed to support people with very severe and extreme responsive behaviours, otherwise known as behavioural and psychological symptoms of dementia, in aged care homes. Methods: A rapid evidence assessment was conducted to inform the evaluation of the Severe Behaviour Response Team (SBRT) service, including a targeted search of peer-reviewed academic literature and an Internet-based search of government, service provider, peak body and university w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Their multivariate analysis showed that the use of electronic identification and RRT intervention was associated with reduced mortality [odds ratio (OR) =0.62; 95% CI: 0.39-0.99; P=0.046], reduced mean ICU length of stay (2.12 days before, 95% CI: 1.97-2.34 vs. 1.95 days after, 95% CI: 1.75-2.06; P<0.001), reduced overall mean length of stay (11.7 days before, 95% CI: 10.9-12.7 vs. 9.9 days after, 95% CI: 9.3-10.6; P<0.001), reduced risk of mechanical ventilation (OR =0.62; 95% CI: 0.39-0.99; P=0.007), and savings on medical costs (per case sepsis was reduced by $7,159; P=0.036) but not vasopressor use (OR =0.89; 95% CI: 0.75-1.06; P=0.18) (22). Other researchers have studied the use of RRTs in patients with dementia (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…Their multivariate analysis showed that the use of electronic identification and RRT intervention was associated with reduced mortality [odds ratio (OR) =0.62; 95% CI: 0.39-0.99; P=0.046], reduced mean ICU length of stay (2.12 days before, 95% CI: 1.97-2.34 vs. 1.95 days after, 95% CI: 1.75-2.06; P<0.001), reduced overall mean length of stay (11.7 days before, 95% CI: 10.9-12.7 vs. 9.9 days after, 95% CI: 9.3-10.6; P<0.001), reduced risk of mechanical ventilation (OR =0.62; 95% CI: 0.39-0.99; P=0.007), and savings on medical costs (per case sepsis was reduced by $7,159; P=0.036) but not vasopressor use (OR =0.89; 95% CI: 0.75-1.06; P=0.18) (22). Other researchers have studied the use of RRTs in patients with dementia (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…13 These teams have often been set up as a pragmatic response to the need to prevent hospital admissions and their theoretical underpinnings of crisis and crisis intervention are not explicit. 14 In addition to the United Kingdom similar services are also being introduced in other nations such as Australia, the United States, Norway, and Flanders (Belgium), 14,15 and therefore research into their suitability has international connotations.…”
Section: Introductionmentioning
confidence: 99%